Conhecimento de famílias ribeirinhas relacionado às infecções sexualmente transmissíveis - LIMA, Nyvia Cristina dos Santos (Universidade Federal do Pará, 2023)
Introduction: Sexually Transmitted Infections are Public Health problems, due to their magnitude and difficulty in accessing adequate treatment. Considering the magnitude and consequences of STIs for the world, it is important to provide and develop studies that allow researchers and managers of public policies and social investments to outline specific, solid and long-term strategies for the transformation of behaviors. In this sense, it is emphasized that it is necessary to implement specific policies so that they contemplate regional realities, peculiarities and specificities of Amazonian riverside communities regarding these infections, the subjects involved and the care practices. Objective: To explore the knowledge of riverine families about Sexually Transmitted Infections. Methodology: Exploratory descriptive research with a qualitative approach. It was carried out in the city of Igarapé-Miri-PA, a riverside community on the Meruú River and is located in the mesoregion of northeast Pará and in the microregion of Cametá and is 78 km away from the capital of Pará, Belém, in the lower Tocantins. Data collection took place in January 2022, through forms. Data were processed in the IRAMUTEQ software and submitted to content analysis. Result: 38 families were interviewed, most of the participants were female, aged between 36 and 59 years old, in a stable union and with different schooling, with emphasis on elementary school. The data pointed to 04 classes, later presented in three categories such as: care practice, knowledge of sexually transmitted infections and accessibility to health services and the availability of treatment. Final considerations: Residents have deficient knowledge about sexually transmitted diseases, whether for prevention or treatment. The care practices mentioned are related to the use of natural resources and presented in the form of bottles and teas, used as an alternative to the scarcity of local primary care services. The lack of accessibility to health services and the conditions of social vulnerability interfere with knowledge, care and continuity of treatment by the public health service.